Pengaruh Promosi, Demosi, Dan Mutasi Jabatan Terhadap Kinerja Pegawai Puskesmas Dalam Pelayanan Kesehatan Masyarakat Di Kota Mamuju - Krisdayanti; Halim, Agus (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the influence of promotion, demotion, and job mutation on employee performance at Community Health Centers (Puskesmas) in Mamuju City. The research adopts a quantitative approach using a survey method. The population consists of all 85 Puskesmas employees; therefore, a census sampling technique was applied. Data were collected using a Likert-scale questionnaire that had previously been tested for validity and reliability. The collected data were analyzed using multiple linear regression to determine the effect of each independent variable on employee performance. The results reveal that job promotion has a positive and significant effect on employee performance. In contrast, job demotion has a negative and significant effect on performance. Meanwhile, job mutation shows a positive and significant influence on employee performance. Simultaneously, promotion, demotion, and job mutation significantly affect the performance of Puskesmas employees in Mamuju City. These findings highlight the essential role of effective career management policies in improving employee performance, which ultimately contributes to better public health service delivery. Therefore, Puskesmas management is expected to implement objective, transparent, and performance-based systems for promotion, demotion, and job mutation in order to motivate employees and optimize organizational outcomes.